An Examination of the Current Value Impact of a Leveraged Buyback Announcement - Farooqi, M. Nauman (Journal of Comparative International Management)

(untitled) (Management Futures, 2004)
Abstract This research is aimed at studying the impact of a substantial share repurchase financed through debt (known as a Leveraged Buyback) on the value of the stock of a company. Prior research shows evidence of a positive average effect, but factors determining the magnitude of response for an individual company are not well understood. This study focuses on explaining variations in response to a leveraged buyback. The study suggested that shareholders like a LBB when the size of the LBB is small and the principle behind it is to supplement their dividend income. However, in cases when the company announces a substantial LBB the shareholders perceive it as bad news. This is because the shareholders feel that such a major restructuring of the capital structure at the hands of an untrustworthy management would put at risk not only their dividend income, but also their original investment.